Aplikasi Media Pembelajaran “PETA KIMIA” Di SMAN Karangpandan Berbasis Android - Melianingsih, Nuning; Gemilang, Romadhon Tanjung (Jurnal Informa : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
Studying chemistry is very important because every process that takes place in our body, be it carbohydrates, proteins, fats, and vitamins, is a chemical process that can produce carbon dioxide gas, water and energy. With knowledge of chemistry we can also maintain personal health and avoid disease. In the current Covid-19 pandemic situation, Indonesian students are required to take part in the learning process online or at home. The students only got an explanation from the teacher using google meet/zoom. Sometimes students are constrained by signals and data packets during the learning process, so they have difficulty receiving explanations from the teacher. One of the subjects that are considered to experience problems is chemistry. From the results of observations at school, the solution to this problem is to create an android application for chemistry subjects which contains material and practice questions. So students can open it again if they still don't understand. Applications created using codular programs because it's easier, faster, and doesn't require a laptop with RAM 8. The final results obtained from making this "CHEMICAL MAP" learning media application, students or users can learn without being limited by time and place. This application can be accessed by admin and user. For admin access rights are the question bank, materials, value data per chapter, practice questions and quizzes. Meanwhile, users can access learning materials, question banks, practice questions and quizzes. The weakness of this "CHEMICAL MAP" learning media application, namely the absence of learning videos and live chat with Chemistry subject teachers.